Reformatting text to a fixed number of columns - Beazley, David M.; Jones, Brian K. 1973- (O'Reilly Media, Inc., 2024)
Build your knowledge of Python with this Shortcuts collection. Focusing on common problems involving text manipulation, many of these tasks can be solved using built-in methods of strings. More complicated operations may require regular expressions or the creation of a full-fledged parser.
Keywords: Python (Computer program language); Python (Langage de programmation)